Five Comedies - Goldoni, Carlo, 1707-1793 (Book collections on Project MUSE., 2016)
Five Comedies collects a selection of Goldoni's finest plays, annotated and translated into English: The New House, The Coffee House, and "The Holiday Trilogy" (Off to the Country, Adventures in the Country, and Back from the Country.